Assessing The Impact Of Curriculum Transformation In Undergraduate Medical Education: Faculty Feedback From Rawalpindi Medical University - Saeed, Ifra; Fatima, Farzana; Ahmed, Amna; Baig, Musharraf; Baig, Areeba (Journal of Rawalpindi Medical College, 2025)
Objective: The objective of this study was to gather and analyze faculty feedback regarding the newly implemented undergraduate MBBS curriculum at Rawalpindi Medical University. The aim was to evaluate faculty satisfaction across areas such as curriculum structure, teaching methods, assessment strategies, policy changes, and institutional support systems. Methods: A cross-sectional survey was conducted in December 2024, involving 31 faculty members from various departments. A structured questionnaire covering six key domains—circular organization, teaching and learning, assessments, policies, technological support, and general feedback—was administered. Responses were collected using a 5-point Likert scale ranging from “Strongly Agree” to “Strongly Disagree.” Data were analyzed using frequency and percentage distributions to identify trends in satisfaction and areas needing improvement. Results: Faculty feedback revealed strong support for the revised teaching strategies, with over 70% approving of both the timely scheduling and integrated teaching formats. Research-related activities were highly appreciated, receiving positive ratings from 81% of respondents. In contrast, assessment methods—particularly their frequency and duration—drew mixed responses, with 38.7% expressing dissatisfaction. A major concern emerged around workload, as only 22.6% found their duties manageable, while over half disagreed, pointing to significant faculty stress. Digital tools such as the Learning Management System (LMS) and biometric systems also received mixed reviews, with a large portion of faculty remaining neutral. Overall satisfaction with the curriculum changes stood at 48.3%, though nearly one-third were undecided and 19.4% expressed dissatisfaction, indicating areas that still require attention. Conclusion: The feedback revealed generally positive perceptions of integrated teaching formats, research activities, and digitalization initiatives. However, concerns were raised about faculty workload, assessment frequency, and the effectiveness of support systems like LMS and biometric tools. While over half of the participants expressed agreement with most reforms, overall satisfaction with the curriculum changes was moderate. These findings highlight the need for continuous dialogue between faculty and curriculum planners to address operational challenges and enhance the efficacy of educational reforms. Keywords: Curriculum evaluation, Faculty feedback , Medical education reform